THE POLICY OF BANNING THE EXPORT OF RAW MATERIALS IN THE MINING SECTOR BY THE INDONESIAN GOVERNMENT FROM THE PERSPECTIVE OF INTERNATIONAL TRADE LAW - Hilton Tarnama P.M.; Ade Marpudin; Belardo Prasetya Mega Jaya (Faculty of Law, Universitas Pekalongan, 2023)
The management and utilization of natural resources by a country are manifestations of exercising national sovereignty. The Doctrine of Sovereignty is designed to provide equality among nations under the law to develop their countries towards prosperity and well-being. The policy of restricting and prohibiting the export of raw materials in the mining sector, such as nickel, gold, and tin, by the Indonesian government, is recognized under international law, particularly international trade law. This policy will bring beneficial impacts to Indonesia's economy. By having the capability to process natural resources independently, Indonesia can enhance its economic self-reliance, reduce dependency on imports, and improve the country's position in the global competition in the mining sector, ultimately leading to increased national revenue and providing greater well-being for the entire Indonesian population.